A Single-visit Approach Using Fillers and Incobotulinumtoxin A: Full Face Enhancement in Asian Patients - Yates Y. Y. Chao, MD (Plastic and Reconstructive Surgery, Global Open, 2018)
Summary:. A 3-dimensional, multi-layered approach combining modalities targeting different manifestations is recommended for achieving optimal esthetic outcomes. To date, studies reporting same-day treatment with dermal fillers and botulinum toxin have not been published. This article documents the practical use of a single-visit, pan-facial multimodal approach in addressing the varying esthetic needs of 8 Asian adults. The case series included male or female patients of varying age and degrees of facial fat, who received combination treatment with calcium hydroxylapatite filler, polydensified hyaluronic acid filler, and incobotulinumtoxin A in a single visit in August 2016 at a treatment center in Taiwan. Treatments were individualized based on the needs of each patient, according to guideline recommendations. The agents, with distinctive rheological properties indicated for different purposes, were applied sequentially across different facial tissue planes within a single visit. Patients were monitored for development of side effects after treatment. Photographs taken before treatment and 2 weeks after treatment were evaluated by the treating physicians. For all patients, treatment produced substantial improvements in all treated facial areas. Inherent morphological deficiencies in younger patients were addressed, age-related changes in older patients were corrected, and facial sexual dimorphism was enhanced in male and female patients. No major side effects occurred after treatment. This case series showcases the real-life implementation of a flexible, single-visit, multimodal approach that can be adapted for a variety of indications.